Integrating Computer-Mediated Peer Review in ESL/EFL Higher Education: A Systematic Review - Nur Arifah Drajati; Dewi Rochsantiningsih; Dewi Cahyaningrum; Ellisa Indriyani Putri Handayani; Endah Kurtianti (AL-ISHLAH: Jurnal Pendidikan, 2023)
This review of the literature gives an overview of how technology has been incorporated into ESL/EFL peer review over the last two decades. Eight peer-reviewed articles contextualized in L2 writing classes were reviewed, capitalizing on Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2010 procedures. This study applied Lai's (2010) three dimensions (perception, process, and product) to classify constructs in research papers. Students favoured integrating technology into peer review as they recognized the significance of giving and receiving peer reviews. Since their teachers did not actively intervene during their interactions, it was convenient for them to exchange and negotiate the reviews. Peer review could therefore encourage their autonomous learning. Concerning the results of the review, they made more comments that were revision-oriented and addressed global issues. The implications for future research are twofold. Pedagogically, teachers should thoroughly prepare their students for integrating new technology into peer-review writing instruction. Effective computerized peer interaction can only occur with teachers' guidance and supervision and the technology's user-friendliness. Practically, teachers can show students proper response rhetoric examples and instruct them on how to create the most valuable, pertinent, and use peer reviews to inform the next revision and useful online comments. Further, the ability to generate qualified feedback is a crucial graduate skill, and as such, higher education curricula should devote far more attention.